¿Do we know how the selection and hiring of a human talent impacts the organization? - Ipanaqué Feria, Andreita del Carmen (2021)
Organizations are currently undergoing disruptive changes, such as business globalization, technological development and development of human talent that lead to greater competitiveness among organizations. Thus, companies, faced with the strong impact of change and the intense movement of organizations in search of quality and productivity, are focusing on improving their personnel selection processes based on competencies to attract and select human talents that add value, innovation and profitability to the company. Therefore, the objective of the article is to highlight the importance of the processes of selection of competencies, and their impact for the organization, the hiring of competent personnel, equipped with human talent for the achievement of unique and sustainable competitive advantages over the competition. That is why, in current times, the competency selection model has greater relevance in the competencies and skills that companies require from professionals, so that they are able to successfully face the challenges of the future, and thus adapt to internal and external changes. Due to the type of research, the present study used is descriptive, because it is based on the description and / or narration of the characteristics of an observed object; and of type Correlation, because it measures the degree of relationship that exists between two or more variables.